Playing politics with science balancing scientific independence and government oversight - Resnik, David B. (Oxford : Oxford University Press, 2009)
Here David B. Resnik explores the philosophical, political, and ethical issues related to the politicalization of science and develops a conceptual framework for thinking about government restrictions on scientific practice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Political aspects; Research -- Moral and ethical aspects; Science and state